Gambaran Faktor Risiko Pasien Kanker Serviks di RSUP Dr. M. Djamil Padang Tahun 2019 - Astri Nadia Hidayat; Novita Ariani; Ida Rahman Burhan (Jurnal Ilmu Kesehatan Indonesia, 2021)
Cervical cancer was one of the most common malignancies in women and was the leading cause of death from cancer, especially in low and middle-income countries (developing countries). The high incidence and mortality rate in developing countries was caused by the lack of knowledge about cervical cancer and limited access to early detection, so that patients come late for treatment and were diagnosed when their condition were severe and the disease had progressed to an advanced stage. This study was conducted in the Medical Record Installation section of Dr. M. Djamil Padang Hospital on 11 August - 2 September 2020. The results of the study were obtained from secondary data from medical records, and data collection was taken by total sampling. Samples that have met the inclusion criteria in this study were 84 patients diagnosed with cervical cancer at Dr. M. Djamil Padang Hospital in 2019. The results showed cervical cancer patients at Dr. M. Djamil Padang Hospital in 2019 were mostly in the ≥50 year age group (51.2%), multiparous category (77.4%), and High School/ equivalent category (70.2 %). Keywords : Risk Factor, Cervical Cancer, Age, Parity, Education Level